Cyclic interface behavior of non-water reactive polymer and concrete during dam restoration. (December 2021) - Wang, Yuke; Han, Musen; Cao, Tiancai; Yu, Xiang; Song, Yingbin
Abstract: In dam restoration engineering, for the differences between material properties from the two sides of the contact surface, complex engineering problems such as excessive shear deformation, separation and sliding of the interface are prone to occur. In this paper, in order to study the mechanical properties of interface between polymer and concrete, the effects of different vertical stresses, shear rates and shear displacement amplitudes were considered, and monotonic direct shear tests and cyclic direct shear tests were conducted by using a newly designed direct shear apparatus. The test results showed that, the polymer-concrete interface shows shear softening in monotonic direct shear and cyclic direct shear tests; when the shear rate and shear displacement amplitude are determined, the average peak shear stress of the polymer-concrete interface shows a good linear relationship with the vertical stress, and the average peak shear stress gradually increases with the increase of vertical stress; with the increase of vertical stress, the shear strength and shear modulus corresponding to the monotonic direct shear and cyclic direct shear tests gradually increased, and the shear strength showed a good linear relationship with the vertical stress; with the increase of shear rate, the shear strength and shear modulus corresponding to the monotonic direct shear and cyclic direct shear tests decrease gradually; the shape of shear stress-displacement curves is remarkably influenced by the shear displacement amplitude.